Literature as a tool for physical geography teaching - Dias, Gabriela Klering; Dias, Liz Cristiane (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
This work proposes to discuss the relationship between Physical Geography and the language of Literature as a proposal of pedagogical practice for Elementary School from the literary work Journey to the Center of the Earth by the French author Júlio Verne. The article aims to propose a pedagogical practice linked to the teaching of Physical Geography and Literature proposed for Elementary School as well as demonstrate the need to use languages ​​for the most critical and realistic teaching of Physical Geography in basic education. As results found, Geography is present in several aspects of the work in question and can be used in a variety of ways, through a fictitious history where with the imaginative aspects of Geography are evidenced. The work demonstrated the importance of languages ​​in the teaching of Geography and the need to expand their use.